2016
DOI: 10.1177/1352458516654310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose vitamin D3 supplementation on antibody responses against Epstein–Barr virus in relapsing-remitting multiple sclerosis

Abstract: Emerging evidence points to a viral infection, low levels of vitamin D and genetics as culprits in multiple sclerosis, but how they combine to cause the disease is unclear. TONY FOUHSE BY C A R O LY N B R O W N © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e. A l l r i g h t s r e s e r v e d. " The genetic contribution doesn't explain even half the risk. " OUTLOOK S 6 | N A T U R E | V O L 5 4 0 | 1 D E C E M B E R 2 0 1 6 MULTIPLE SCLEROSIS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
1
33
0
2
Order By: Relevance
“…Baseline characteristics of the study population are shown in Table 1. As reported previously [28] there were no group differences in age, body mass index (BMI), smoking, use of disease modifying drugs, disability as measured by EDSS, calcium intake or relapse rate the previous year. The serum concentration of 25(OH)D increased to 123.2 ± 34.2 nmol/L at week 96 in the vitamin D group, and to 61.8 ± 25.2 nmol/L in the placebo group.…”
Section: Resultssupporting
confidence: 63%
“…Baseline characteristics of the study population are shown in Table 1. As reported previously [28] there were no group differences in age, body mass index (BMI), smoking, use of disease modifying drugs, disability as measured by EDSS, calcium intake or relapse rate the previous year. The serum concentration of 25(OH)D increased to 123.2 ± 34.2 nmol/L at week 96 in the vitamin D group, and to 61.8 ± 25.2 nmol/L in the placebo group.…”
Section: Resultssupporting
confidence: 63%
“…However, this reduction was not observed after 96 weeks, suggesting that high-dose oral vitamin D3 supplementation may only lead to a transient increase in the amount of 1,25 (OH)2D available in immune cells. 86 Viral infections may further up-regulate CYP27B1 by converting more circulating vitamin D to its active form and therefore synergize with vitamin D to induce cathelicidin at the site of infection or injury. 87 The level of vitamin D was also shown to be negatively correlated with HBV-DNA levels in patients with chronic hepatitis B, suggesting that deficient vitamin D status may be related to the development of increased viral replication and reduced HBV-mediated immune responses.…”
Section: A Potential Role For Vitamin D In B-lymphocyte-related Disormentioning
confidence: 99%
“…In support of this observation, reduced levels of antibodies against EBV nuclear antigen (EBNA)‐1 has been found following 48 weeks of high‐dose oral vitamin D3 supplementation in MS patients. However, this reduction was not observed after 96 weeks, suggesting that high‐dose oral vitamin D3 supplementation may only lead to a transient increase in the amount of 1,25 (OH)2D available in immune cells …”
Section: Introductionmentioning
confidence: 98%
“…Others correlate vitamin D with EBV load . There are publications that claim that vitamin D supplementation reduces anti‐EBNA‐1 titres, but they use high concentrations (higher than the serum concentrations of our patients) and the effect seems to be temporary (there is a decrease in antibody titres after 48 weeks, but it disappears after 96 weeks) .…”
Section: Discussionmentioning
confidence: 88%